Adaptive Full Order Sliding Mode Control for Electrical Motor Drive - Pham Thanh-Binh; Cao Tran Ngoc-Tuan; Nguyen Tan-No; Truong Nguyen-Vu (E3S Web of Conferences)
This paper presents an adaptive full order sliding mode control scheme for electrical motor drive. Within this scheme, the discontinuous switching function is placed at the first derivative of the control signal and its associated gain is now dependent on the respective sliding mode manifold, yielding substantial reduction / elimination of the “chattering” phenomenon. The simulation study demonstrates the effectiveness of the proposed approach.